Use of controlled exogenous stress for improvement of poly(3-hydroxybutyrate) production in Cupriavidus necator - Obruca, S; Marova, I; Svoboda, Z; Mikulikova, R (Folia microbiologica, 2010)
The PHB production by Cupriavidus necator H16 depends on the type and concentration of stress factors and on the time of stress application. Hydrogen peroxide and ethanol significantly enhanced PHB accumulation in C. necator cells. Improved yields (10.9 g/L PHB) were observed after exposure of bacterial culture to 0.5 mmol/L H2O2 at the beginning of cultivation and to additional peroxide stress (5 mmol/L H2O2) after 60 h of cultivation (beginning of the stationary phase). Production was then approximately 28 % higher than in control (8.50 g/L PHB). The highest yields (11.2 g/L PHB) were observed when ethanol (0.5 %) was applied at the beginning of stationary phase. An application of exogenous stress could thus be used as a simple strategy for a significant improvement of PHB production in C. necator.
Keywords: Stress, Physiological; fyziologický stres; Cupriavidus necator; ethanol; Ethanol; polyestery; Hydroxybutyrates; hydroxybutyráty; peroxid vodíku; Hydrogen Peroxide; Polyesters